2021
DOI: 10.1002/qute.202100061
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐Device Entanglement in a 65‐Qubit Superconducting Quantum Computer

Abstract: The ability to generate large-scale entanglement is an important progenitor of quantum information processing capability in noisy intermediate-scale quantum (NISQ) devices. In this paper, the extent to which entangled quantum states over large numbers of qubits can be prepared on current superconducting quantum devices is investigated. Native-graph states on the IBM Quantum 65-qubit ibmq_manhattan device and the 53-qubit ibmq_rochester device are prepared and quantum readout-error mitigation (QREM) is applied.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…As a result of measurement errors, actual quantum states and channels are often more similar to expected states and channels than tomography results would suggest. Since measurement errors on IBM quantum processors are mostly classical 22 , quantum readout error mitigation can be used to obtain tomography results which more accurately reflect the prepared states and channels, as has been successfully done in a number of recent studies which also involved measurements on highly entangled states on IBM quantum processors 32 34 . To mitigate readout errors in a n -qubit experiment (the main experiment), we first use quantum detector tomography 35 to construct a by calibration matrix .…”
Section: Introductionmentioning
confidence: 99%
“…As a result of measurement errors, actual quantum states and channels are often more similar to expected states and channels than tomography results would suggest. Since measurement errors on IBM quantum processors are mostly classical 22 , quantum readout error mitigation can be used to obtain tomography results which more accurately reflect the prepared states and channels, as has been successfully done in a number of recent studies which also involved measurements on highly entangled states on IBM quantum processors 32 34 . To mitigate readout errors in a n -qubit experiment (the main experiment), we first use quantum detector tomography 35 to construct a by calibration matrix .…”
Section: Introductionmentioning
confidence: 99%
“…121 Later, Mooney et al 122 have generated and verified 27-qubit GHZ states with a fidelity of 0.546 ± 0.017 on the quantum computer ibmq_montreal 123 after quantum readout error mitigation, with a detectable improvement in fidelity after parity verification. The same investigators 124 have demonstrated entanglement of all 53 qubits on ibmq_rochester 125 and all 65 qubits on ibmq_manhattan. 126 Earlier, Sager, Smart, and Mazziotti 127 had prepared states interpretable as exciton condensates of photon particles and holes on ibmq_rochester, using 53 qubits.…”
Section: Introductionmentioning
confidence: 92%
“…To investigate the effect this has on our results we re-run our simulation with a noise model [1]. To reduce the impact of these errors we implement a measurement error mitigation technique [20] recently demonstrated in the context of verifying whole-array entanglement in the IBM Quantum ibmq_manhattan device [17]. This procedure consists of performing an initial calibration of the basis states for the noisy device.…”
Section: Simulations With Noise and Error Mitigationmentioning
confidence: 99%